Study on the relationship between unanticipated water and soil disasters and landuse - CHEN He-ping; WANG Shen-fa; HU Xian-song (浙江大学学报. 农业与生命科学版, 2002)
In this paper the relationship between unanticipated water and soil disaster and landuse in Qingyuan county was studied. The results showed that the amount of disasters on woodland was the largest, especially on pine and fir woodland. However, there was no disasters happened on natural evergreen broad-leaved forest and timber-available phyllostachys pubescens forest. It was farmland that had the highest disaster density, and the sloping dryland ranked the first of the secondary landuse types, followed by irrigated rice paddy. So, to prevent mountainous disasters, reforesting of the dry sloping cultivated must been adapted. In southern mountain areas, closing hillsides to facilitate afforestation was the effective measure to avoid mountainous disasters, and growing timber-available phyllostachys pubescens forest was an effective approach to develop ecological economy.